Study on the seawater cooled PRHRS of a nuclear propulsion ship with the upper heat exchanger for driving force and the seawater heat exchanger as an ultimate heat sink - Yong Hwan Yoo; Han Koo Jeong; Wooseong Park; Soo Hyoung Kim; Yong Hoon Jeong (International Journal of Naval Architecture and Ocean Engineering, 2024)
As international maritime trade among countries increases, great efforts are being made to reduce the amount of greenhouse gases emitted from ships using conventional fossil fuels. A variety of environment-friendly power sources for ships are being considered, and nuclear energy is one of them. The research described in this paper focuses on elemental technologies related to nuclear-powered ships rather than the nuclear reactor technology itself. Among those technologies, the Passive Residual Heat Removal System (PRHRS) of a nuclear-powered ship is studied to remove residual heat by using seawater as an alternative heat sink. New concept of PRHRS is proposed and it is named as SWC-PRHRS. SWC-PRHRS has two heat exchangers: one is for driving force and another is for dumping the most of residual heat to the sea. Numerical analysis and experimental studies are conducted to improve the performance of SWC-PRHRS. The numerical results show that most of the residual heat comes from a reactor core is eliminated by sea water cooling proving the concept of SWC-PRHRS is working properly without any operator intervention and additional water supply. Experimental studies are conducted based on the numerical analysis results. From the experimental results, it is found that the mass flow rate of SWC-PRHRS is very sensitive to the filling ratio of SWC-PRHRS and there are three distinctive filling ratio ranges. Through the experiment, it is confirmed that SWC-PRHRS is working efficiently with the lower mass flow rate and the smaller upper heat exchanger without any operator intervention. SWC-PRHRS could remove a large amount of residual decay heat from the ship's reactor and release it to the sea. Considering the size, weight, and exceptional heat removal capability of SWC-PRHRS, it is clear that SWC-PRHRS is well suited for marine application usage.